2018
DOI: 10.1089/pho.2017.4367
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Photoselective Vaporization of the Prostate with 120 W 532 nm Laser in Patients with Benign Prostatic Hyperplasia on Anticoagulation or Antiplatelet Therapy: Observations on Long-Term Outcomes

Abstract: Our results demonstrate that PVP for patients with BPH is an effective and safe procedure with satisfactory long-term outcomes. Anticoagulant and antiplatelet drugs did not significantly influence the results, or the complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A total of 3450 distinctive studies were found, of which 19 studies (between 1996 and 2021) satisfied the inclusion criteria and were comprised in the study. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] This metaanalysis study based on 19 studies included 5715 benign prostatic hyperplasia subjects at the start of the study; 1501 of them were on anticoagulant/antiplatelet therapy, and 4214 were control. All studies evaluated the safety of benign prostatic hyperplasia wound after surgical removal in subjects on anticoagulant or antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3450 distinctive studies were found, of which 19 studies (between 1996 and 2021) satisfied the inclusion criteria and were comprised in the study. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] This metaanalysis study based on 19 studies included 5715 benign prostatic hyperplasia subjects at the start of the study; 1501 of them were on anticoagulant/antiplatelet therapy, and 4214 were control. All studies evaluated the safety of benign prostatic hyperplasia wound after surgical removal in subjects on anticoagulant or antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3450 distinctive studies were found, of which 19 studies (between 1996 and 2021) satisfied the inclusion criteria and were comprised in the study 10‐28 . This meta‐analysis study based on 19 studies included 5715 benign prostatic hyperplasia subjects at the start of the study; 1501 of them were on anticoagulant/antiplatelet therapy, and 4214 were control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the feasibility of using local anesthesia during 80-Watt PVP has been previously evaluated [6] , there are no such data for 180-Watt PVP. The fibers used in this new system are water cooled, which reduces laser energy in case of overheating [14,15] . This technology may explain the more favorable outcome of pain recorded for our patients compared with those in previous studies, in which prostatic block was used for transurethral prostate procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The hemostasis of green lasers is excellent, which allows PVP appling to patients of BPH with anticoagulant therapy. [ 18 ] PVP also applies to large-volume prostate patients. A study was performed to evaluate the results of GreenLight XPS photovaporization (PVP/XPS) with intraoperative transrectal ultrasonographic monitoring for the treatment of large BPH, with volume >80 ml.…”
Section: Edical L Asersmentioning
confidence: 99%